2011
DOI: 10.1007/s00414-010-0544-3
|View full text |Cite
|
Sign up to set email alerts
|

Age and gender-dependent bone density changes of the human skull disclosed by high-resolution flat-panel computed tomography

Abstract: Bone density decay only theoretically provides a new method to determine age at death for adult females. Due to the scattering of the data, an accuracy of approximately ±18 years is found at a confidence interval of 75%, which is, unfortunately, of limited practical interest. We found new sex differences of bone density decay in the skull that are potentially of relevance for the general understanding of bone degradation processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 53 publications
4
20
0
Order By: Relevance
“…Previous studies have only shown a general and insignificant trend of increased skull thickness with age, although there is a statistically significant relationship between cortical thinning and age for the inner and outer tables of the skull in females [44]. Similarly, regarding skull density, male skull bone density remains constant with age while female skull bone density decays slowly starting at 20 years of age [45]. Given that the majority of our modeling population is male, we believe that the variations in intracranial pressure maps observed between individuals are largely due to the morphological differences in skulls between individuals.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have only shown a general and insignificant trend of increased skull thickness with age, although there is a statistically significant relationship between cortical thinning and age for the inner and outer tables of the skull in females [44]. Similarly, regarding skull density, male skull bone density remains constant with age while female skull bone density decays slowly starting at 20 years of age [45]. Given that the majority of our modeling population is male, we believe that the variations in intracranial pressure maps observed between individuals are largely due to the morphological differences in skulls between individuals.…”
Section: Discussionmentioning
confidence: 87%
“…Two previous studies examined gender and age with respect to skull anatomy [2,3]. These reported a statistically significant correlation between skull density (in HU) and age for female skulls but not males.…”
Section: Comparison To Previous Studiesmentioning
confidence: 94%
“…The human cranium has been studied from many perspectives, ranging from forensics [1][2][3] fracture mechanics [4], developmental anatomy [5,6] to acoustics [7][8][9][10] and radiology [11]. Now, the emerging field of transcranial focused ultrasound (TcFUS) [12] brings a new set of reasons to examine the material properties of the human skull.…”
Section: Introductionmentioning
confidence: 99%
“…In this initial study, the skull collection was used to investigate whether the degree of closure of the sagittal suture could be used to estimate aad. When this approach proved ineffective [16], we decided to use the acquired dataset collection to investigate if the radiological determination of skull bone density, based on the attenuation of x-rays in a CT acquisition, might instead allow an estimate of aad [17,18]. In this investigation, we discovered an unexpected sex difference: while the bone density of adult female skull caps was found to diminish slightly with increasing age, the bone density of adult male skull caps remained constant.…”
Section: Introductionmentioning
confidence: 81%